2014
DOI: 10.1007/s10654-014-9952-x
|View full text |Cite
|
Sign up to set email alerts
|

BiomarCaRE: rationale and design of the European BiomarCaRE project including 300,000 participants from 13 European countries

Abstract: Biomarkers are considered as tools to enhance cardiovascular risk estimation. However, the value of biomarkers on risk estimation beyond European risk scores, their comparative impact among different European regions and their role towards personalised medicine remains uncertain. Biomarker for Cardiovascular Risk Assessment in Europe (BiomarCaRE) is an European collaborative research project with the primary objective to assess the value of established and emerging biomarkers for cardiovascular risk prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 35 publications
(45 reference statements)
0
73
0
1
Order By: Relevance
“…The present study is a substudy of the BiomarCaRE consortium 13. Current analyses include BiomarCaRE cohorts with available information on AF status at baseline and follow-up (DanMONICA, FINRISK, Moli-sani and Northern Sweden), totaling N=79,793 individuals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study is a substudy of the BiomarCaRE consortium 13. Current analyses include BiomarCaRE cohorts with available information on AF status at baseline and follow-up (DanMONICA, FINRISK, Moli-sani and Northern Sweden), totaling N=79,793 individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Our study comprises a subset of the BiomarCaRE (Biomarker for Cardiovascular Risk Assessment in Europe) consortium, which provides information on the epidemiology of AF and its risk factors in European community cohorts 13. Our objective was to systematically examine sex differences in AF incidence, and in the association of AF with mortality, classical cardiovascular risk factors and biomarkers in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…We applied a targeted quantitative metabolomic approach to analyze the rat plasma samples using the Biocrates Absolute IDQ ® p180 kit (Biocrates Life Sciences AG, Innsbruck, Austria). This kit covers endogenous metabolites playing pleiotropic roles in bioenergetics metabolism, cell signaling, and cell structures and previously involved in numerous diseases including cardiovascular ones …”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies have demonstrated the association between the risk of major cardiovascular events and detectable, presumably still normal, cTn values measured with highly sensitive cTnI and cTnT assays [110][111][112][113]147]. These studies give rise to the question of whether there is a myocardial injury threshold beyond which individual risk increases thus being of potential clinical utility in cardiovascular risk prediction.…”
Section: Clinical Relevance Of Gender-specific Decision Values For Ctmentioning
confidence: 99%